DNase and Gelatinase Activities Of β-Hemolysin Aeromonas hydrophila Isolated from Catfish (Clarias batrachus) - Rahayu Kusdarwati; Muhamad Amin; Aldiansyah Budi Wardana (Department of Aquaculture, 2021)
Aeromonas hydrophila infection can cause mass mortality fish and result economic losses for farmers. These is bacterium secretes substances or compounds that support its virulence by producing toxins and extracellular proteins in the form of enzymes. This study aimed to determine the activity of β-hemolysin toxin, DNase enzyme and gelatinase enzyme of A. hydrophila isolated from catfish (Clarias batrachus) in Sidoarjo. This research was carried out in November 2020 in Dukuh Tengah Village, Buduran District, Wedoro Village, Waru District, Wadung Asri Village, Waru District and Keboan Sikep Village, Gedangan District. The sampling technique was carried out by researchers by following activities in the field and visiting correspondents directly in the catfish cultivator ponds, then the catfish samples were carried out by biochemical tests and toxin and enzyme activity tests to obtain the information and data needed. The results showed that A. hydrophila bacteria in catfish produced positive β-hemolysin toxin, DNase enzyme and gelatinase enzyme. The conclusion of the research was that 10 isolates of A. hydrophila bacteria isolated from catfish (Clarias batrachus) in Sidoarjo showed the activity of β hemolysin toxin, DNase enzyme and gelatinase enzyme.